2020
DOI: 10.1371/journal.pone.0243627
|View full text |Cite
|
Sign up to set email alerts
|

Factors mediating the pressor response to isometric muscle contraction: An experimental study in healthy volunteers during lower body negative pressure

Abstract: Whilst both cardiac output (CO) and total peripheral resistance (TPR) determine mean arterial blood pressure (MAP), their relative importance in the pressor response to isometric exercise remains unclear. This study aimed to elucidate the relative importance of these two different factors by examining pressor responses during cardiopulmonary unloading leading to step-wise reductions in CO. Hemodynamics were investigated in 11 healthy individuals before, during and after two-minute isometric exercise during low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Cold pressor test (CPT) is a model of acute pain, where typically a hand is immersed in ice-cold water (Wolf & Hardy, 1941). CPT stimulates thermoreceptors and nociceptors (Patapoutian et al, 2003), causing increased sympathetic nervous activity (Victor et al, 1987) and a rise in arterial pressure, peripheral resistance, HR, and cardiac output (Stens et al, 2020;Stocks et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Cold pressor test (CPT) is a model of acute pain, where typically a hand is immersed in ice-cold water (Wolf & Hardy, 1941). CPT stimulates thermoreceptors and nociceptors (Patapoutian et al, 2003), causing increased sympathetic nervous activity (Victor et al, 1987) and a rise in arterial pressure, peripheral resistance, HR, and cardiac output (Stens et al, 2020;Stocks et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…TPR has been previously suggested to provide a less active contribution to this BP rise, although the limited previous data have been largely based on transitory measures as opposed to continuous recording which may not be sufficient to effectively capture the true pressor response [130,147,149,150]. Examining the current continuous data, handgrip research has demonstrated a small increase in TPR that remains above baseline when measured throughout a single contraction [151], as well as when measured throughout a 4 × 2-min protocol session [62]. Conversely, the wall squat appears to produce an initial rise in TPR, followed by a stepwise reduction throughout each interval [96,97].…”
Section: Physiological Responses During Isometric Exercisementioning
confidence: 76%
“…Although LBNP mainly affects and reduces cardiac output, small changes in MAP may be seen. Conversely, IHG mainly increases MAP but may also slightly increases cardiac output (Stens et al 2020 ). The regression models therefore attempt to describe the effect of one variable, controlling for the other.…”
Section: Discussionmentioning
confidence: 99%